Evaluation of differential white blood cell count and cheek pouch epithelium in 7,12-dimethylbenza[a]anthracene hamster carcinogenesis model, managed with three phytochemicals - Darwish Mahmoud; Hassan Magda; Maria Ola M. (EDP Sciences, 2023)
Objectives: Nigella sativa (NS), thymoquinone (TQ), and epigallocatechin-3-gallate (EGCG) are phytochemicals that might have antioxidant protective potentials on the hamster cheek pouch epithelium (HCPE). We aimed at evaluating and comparing the potential therapeutic outcomes of these 3 phytochemicals by analysis of peripheral white blood cells (WBCs) counts. Materials and Methods: NS whole oil, TQ and EGCG were administered before, with or after 7,12-dimethylbenza[a]anthracene (DMBA) painting the hamster left cheek pouch. Before sacrificing each animal, 2 ml of blood was withdrawn into a fine heparin-containing tube to estimate the total WBCs, lymphocytes, MID cells, and granulocytes counts by an automatic count system. All cheek pouches were surgically excised and examined with light microscope. Results: Severe epithelial dysplasia was evident after 6 weeks of DMBA administration, and when NS was given for 2 weeks followed by DMBA for 6 weeks. When NS or EGCG were given for 2 weeks then continued with DMBA for 6 weeks, mild dysplasia was seen. When DMBA was given for 6 weeks followed by NS or TQ for 6 weeks, mild dysplasia was noted. Administration of DMBA for 6 weeks resulted in significant reduction in total WBCs and lymphocytes counts compared to healthy controls. Administration of NS or TQ for 2 weeks resulted in significant elevation in lymphocytes count compared to healthy controls. Significant elevation in total WBCS and lymphocytes counts was noted when EGCG was given for 2 weeks and continued with DMBA for other 6 weeks. Similar results were noted when DMBA was given for 6 weeks followed by TQ for 6 weeks when compared to NS, DMBA or healthy controls. Discussion: The three phytochemicals showed different levels of protection against DMBA carcinogenic activity, more specifically, TQ and NS had higher therapeutic potential and might be used for treatment and/or preventive management of oral cancer in the future. Conclusion: However, further investigations are required to address the mechanism of action and feasibility of clinical application of each phytochemical.